El soneto CXLVIII de Tetrarca traducido por Enrique de Villena: ¿original o traducción? - Rubio Tovar, Joaquín (Cuadernos de Filología Italiana, 2005)
The translation of the sonnet which appears on pages 195-198 of the Manuscript 10186 held at the National Library in Madrid is perhaps the first trace of Petrarch’s Canzoniere in Spanish. The exegesis which accompanies this manuscript provides some ideas and concepts which help us to understand the literature written between 1400 and 1430. This exegesis also serves to ascertain the knowledge of the translator as well as the scholiast’s interpretation. Translations should not be judged only by their accuracy, but should also be evaluated on the basis of their reception and the intention with which they were prepared. The information provided by the translation, and its views on literature and culture, are more valuable than mere transcription of the original Italian text, which the Marquis also held in his library. This reassessment of translation raises a permanent debate. Do literary works possess a meaning of their own, regardless of the way they are received by readers? Or does the meaning of a literary work depend on the way it is read, translated and rewritten?